Changing identities: tRNA duplication and remolding within animal mitochondrial genomes - Rawlings, Timothy A. (National Academy of Sciences, 2003)
Although the majority of metazoan mitochondrial genomes (mtDNAs) contain the same 37 genes, including 22 encoding transfer RNAs (tRNAs), the recognition of orthologs is not always straightforward. Here we demonstrate that inferring tRNA orthologs among taxa by using anticodon triplets and deduced secondary structure can be misleading: through a process of tRNA duplication and mutation in the anticodon triplet, remolded leucine (L(UUR)) tRNA genes have repeatedly taken over the role of isoaccepting L(CUN) leucine tRNAs within metazoan mtDNA. In the present work, data from within the gastropods and a broad survey of metazoan mtDNA suggest that tRNA leucine duplication and remolding events have occurred independently at least seven times within three major animal lineages. In all cases where the mechanism of gene remolding can be inferred with confidence, the direction is the same: from L(UUR) to L(CUN). Gene remolding and its apparent asymmetry have significant implications for the use of mitochondrial tRNA gene orders as phylogenetic markers. Remolding complicates the identification of orthologs and can result in convergence in gene order. Careful sequence-based analysis of tRNAs can help to recognize this homoplasy, improving gene-order-based phylogenetic hypotheses and underscoring the importance of careful homology assessment. tRNA remolding also provides an additional mechanism by which gene order changes can occur within mtDNA: through the changing identity of tRNA genes themselves. Recognition of these remolding events can lead to new interpretations of gene order changes, as well as the discovery of phylogenetically relevant gene dynamics that are hidden at the level of gene order alone.